The effects of task complexity and task condition on L2 individual writing and peer interaction / Soh Siak Bie - Soh , Siak Bie (2020)
This study adopts the Cognition Hypothesis to examine the effects of task complexity, (+/- causal reasoning demand) and task condition (individual, dyadic and triadic groupings) on the L2 individual writing and peer interaction. A 2 (Task Complexity) x 3 (Task Condition) repeated-measures ANOVA (RM-ANOVA) research design, was employed on 36 Malaysian university students. Six argumentative topic-based written texts were produced by each participant in each of the three sessions. In each of the sessions, i.e. individual, dyadic and triadic, participants experienced two argumentative tasks: one simple and another complex based on the principle of natural complexity progression. The individual session was set as baseline data to compare results of the Second Language (L2) individual writing and peer interaction in dyadic and triadic conditions. For the dyadic and triadic sessions, participants first discussed each of the simple and complex topics given and then proceeded to write on each topic individually. In total, 216 written texts were analysed for lexical and syntactic Complexities, morphosyntactic Accuracy and Fluency (CAF) while transcripts of interaction totalling 15 hours were analysed in terms of Negotiation of Meaning (NoM), Language-Related Episodes (LREs) and uptakes of recast. Results of CAF on the L2 individual written production revealed that task complexity is statistically significantly different for certain dimensions of lexical and syntactic complexities, accuracy, text length but not for fluency. Task condition on the other hand, is statistically significantly different for the measures of lexical and syntactic complexities except for certain dimensions of complexities, like coordinate clause per T-unit, and accuracy, error-free clauses (EFC). For L2 individual writing, tasks that are more complex produced lengthier texts with higher accuracy, EFC and greater syntactic complexity, for mean length of clause (MLC), but not for dependent clause per clause (DCC). As for task condition, triadic grouping produced lengthier texts with higher lexical complexity, for mean segmental type/ token ratio-50 (MSTTR-50) and greater syntactic complexity, for MLC. As for the measure of DCC, dyadic grouping produced dependent clauses that are more varied in the simple task. The baseline data of the individual session produced more fluent L2 individual writing, as compared to dyads followed by triads. Results of the measures of NoM, LREs and Uptakes on the peer interaction revealed that L2 learners in triadic grouping produced higher comprehension checks when negotiating meaning with peers. It also showed that dyadic grouping produced higher partially or incorrectly resolved LREs and unmodified uptakes of recast. In conclusion, the findings lent partial support to Robinson’s Cognition Hypothesis that cognitively more complex tasks increased the L2 production of certain dimensions of lexical and syntactic complexities, like MSTTR-50, MLC and accuracy, EFC. As for the finding of the dimension of syntactic complexity, DCC, it seemed to have a trade-off effect as proposed by Skehan’s Trade-off Hypothesis. Task condition with more number of participants assigned for peer interaction prior to L2 learners’ individual writing seemed to contribute to higher MSTTR-50, MLC and EFC.